IMPLIKATUR DALAM TUTURAN INTEROGATIF PADA ANIME DETECTIVE CONAN (MEITANTEI CONAN) - Yustika Dewi, Maya Silvia; Aibonotika, Arza; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research discusses about implicatures in interrogative utterances on Anime Detective Conan (Meitantei Conan). The purpose of this research is to explain what the meaning and intent of implicatures are in interrogative utterances on anime. The research uses the theory proposed by Grice (1975) on implicature and uses the analysis theory means-end by Geoffrey Leech (1993). The research method uses is a qualitative descriptive method. The data is obtained by listening to the conversations spoken by the characters. Then the interrogative utterances containing implicatures will be recorded and marked. The results of this study found as many as 25 implicature data in interrogative utterances, namely commanding implicatures, complaining implicatures, mocking implicatures, insinuating implicatures, suggesting implicatures, and affirming implicatures. It can be concluded that the implicature in interrogative utterances is used to maintain politeness in conversation.Key Words: Implicature, Interrogative Utterances, Theory Means-End, Detective Conan,Japanese Anime